Pengembangan Instrumen Evaluasi Program Prakerin Kompetensi Keahlian TKJ di SMK - Azmil Azman; M. Giatman; Ambiyar; Syahril (Cakrawala: Jurnal Pendidikan, 2020)
Evaluation of the Internship instrument development program is an instrument that has been developed and then used to evaluate an Internship program of TKJ competencies in Vocational Schools which includes input components such as students, productive teachers, curriculum, and Sarpras, process components including student readiness, companion teacher performance, companion performance in the business and industrial world, the output of the Internship program benefits students and the business world and the industrial world. This research approach uses the Research & Development Model according to (Borg, WR & Gall, M D. (2003)). In collecting data using a questionnaire, interview, observation, and documentation instrument. The validity of the instrument was analyzed by bivariate correlations between the scores of each indicator with the total score, the reliability of the instrument was analyzed by using the alpha Cronbach. This study showed a result including input components 98,9%, process 96,6%, and product 96,7%, the instrument developed was valid and classified as very good, the reliability coefficient of student questionnaire 0.963, productive teacher 0,981, accompanying teacher 0,942, business associate and industrial world 0,961.